Sistema de medição para oximetria de pulso - Andrade, Luiz Augusto Kalva de (2009)
The main subject of this research is the development of a measurement system for pulse oximetry in order to determine oxygen arterial saturation. The measurement of blood oxygen saturation is recognized as a world standard in anesthesiology care, being used in intensive care units as well as in veterinary surgery. The developed oximetry system employs a transmittance probe using light emitting diodes and a photo detector as main components. The instrument is also composed by a transimpedance amplifier, demux and sample-and-hold circuits, pass-band filters, digitally controlled amplifier and a digital signal processor. The functioning results of the prototype were confirmed by using a commercial pulse oximeter simulator, obtaining a coefficient r = 0.99954 between the oxygen saturation data. Also, in vivo results obtained were compared with a commercial pulse oximeter showing mean differences of ±1.67% for percentage saturation data and ±1.44 beats per minute for heart rate. It is hoped that this work can help to improve the oxygen monitoring to body tissues and to make pulse oximetry a more common and accessible monitoring technique.